Cocatalyst free nickel sulphide nanostructure for enhanced photocatalytic hydrogen evolution. (26th January 2022) - Muniyappa, Murthy; N. Kalegowda, Sagara; Shetty, Manjunath; Sriramoju, Jagadeesh Babu; Shastri, Mahesh; S.V., Navakoteswara Rao; De, Debasis; M.V., Shankar; Rangappa, Dinesh
Abstract: Metal chalcogenides are highly active, inexpensive, and earth-abundant materials for photocatalytic hydrogen evolution. This work presents cocatalyst-free Nickel Sulphides (α and β phases) nanostructures for photocatalytic hydrogen generation. NiS nanostructures are synthesized by the solvothermal method by varying the water to ethanol ratio. The synthesized sample has shown an optical bandgap of 1.83 eV, which is favorable for H2 generation. X-ray diffractometer (XRD) patterns confirm the formation of hexagonal and rhombohedral crystal structures with high phase purity for both NiS-α and NiS-β nanostructures. The multifaceted regular-shaped morphology with 50 nm sized particles was confirmed by high-resolution transmission electron microscopy (HR-TEM). The photocatalytic H2 generation studies reveal that the NiS-α phase exhibited better H2 generation activity of 13.413 m mol h −1 g −1 than the NiS-β phase of 12.713 m mol h −1 g −1 under UV–Vis light irradiation without any cocatalyst. Graphical abstract: Image 1 Highlights: Synthesized NiS-α/β phase by simple solvothermal method. By changing the water to ethanol ratio bandgap of NiS varied from 1.83 to 1.53 eV. NiS-α phase exhibited H2 generation of 13.413 mmol h −1 g −1 . NiS acts as alternative photocatalyst to binary or ternary photocatalysts.